2021
DOI: 10.3390/photochem1010004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoluminescence of Electrodeposited Europium Complex on Bare and Terpyridine-Functionalized Porous Si Surfaces

Abstract: The trivalent Eu(III) ion exhibits unique red luminescence and plays an significant role in the display industry. Herein, the amperometry electrodeposition method was employed to electrodeposit Eu(III) materials on porous Si and terpyridine-functionalized Si surfaces. The electrodeposited materials were fully characterized by scanning electron microscopy, X-ray diffraction crystallography, Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy. Photoluminescence (PL) spectroscopy reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Other CV profiles (Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Yb mixed Eu ions) showed the curvature between −1.4 V and −1.2 V. The peak position (±0.01 V) was determined by the intersection point of the two crossing lines as depicted in the corresponding CV profile in Figure 1. Joo et al also observed similar CV profiles for Ln (III) ions on carbon, Ni, and porous Si electrodes [21][22][23]. There was a weak inclination that the CV peak became slightly shifted to a positive direction, as shown in Figure 1n.…”
Section: Methodssupporting
confidence: 56%
See 4 more Smart Citations
“…Other CV profiles (Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Yb mixed Eu ions) showed the curvature between −1.4 V and −1.2 V. The peak position (±0.01 V) was determined by the intersection point of the two crossing lines as depicted in the corresponding CV profile in Figure 1. Joo et al also observed similar CV profiles for Ln (III) ions on carbon, Ni, and porous Si electrodes [21][22][23]. There was a weak inclination that the CV peak became slightly shifted to a positive direction, as shown in Figure 1n.…”
Section: Methodssupporting
confidence: 56%
“…57) to Yb (No. 70) [21][22][23]. For Eu (III) ions, the CV peak position was observed to be around −0.9 V, about −0.3 V lower than other Ln (III) ions.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations